The Utilization Optimizing of Productive Zakat inImplementation Sustainable Development Goals to Improve Mustahik’s Welfare - Shofa Fadillah Rindjani; Rahmini Hadi (Profesional Muda Cendekia Publishing, 2022)
Inequality can be minimized by an equitable redistribution of wealth. Optimal utilization of zakat provides an alternative so that it can support the welfare of the community. BAZNAS has a program institution called ZCD, a program with a focus on empowerment through communities or villages. ZCD in Wlahar Wetan Village carries out integrated agricultural activities, which combine the concepts of animal husbandry and agriculture. The relationship between zakat and the Sustainable Development Goals (SDGs) can be seen from one of its goals, namely poverty alleviation. This study aims to determine the implementation that occurs between zakat, especially the ZCD program with the SDGs and to examine the optimization of the utilization of productive zakat on the ZCD program in Wlahar Wetan Village and see the welfare of the beneficiary mustahik families. The results of the study show that the role of zakat is not only as a source of funding for the SDGs program, but the relevance of program objectives, stakeholders, being a medium for Islamic da'wah to the world, as well as full support from several institutions to support the SDGs goals. Optimization has appeared in the ZCD program in Wlahar Wetan Village with a traditional productive utilization pattern which has been seen in increasing the welfare of mustahik families who have reached the Prosperous Family I (KSI) stage according to the BKKBN.